Apparent digestibility of animal, plant and microbial ingredients for Pacific white shrimp Litopenaeus vannamei. (13th October 2017) - Qiu, X.; Nguyen, L.; Davis, D.A.
Abstract: A digestibility trial was conducted to determine apparent digestibility coefficients of dry matter, protein, energy and amino acids of animal, plant and microbial ingredients for Pacific white shrimp, Litopenaeus vannamei . The tested ingredients included traditional soybean meal (TSBM), PepsoyGen soybean meal (PSBM), NutriVance soybean meal (NSBM), fish meal (FM), poultry meal (PM), squid hydrolysis (SQH), scallop hydrolysis (SCH), flash dried yeast (FDY), two batches of Ulva meal (UMF and UMS) and bacteria biomass (BB). A basal diet was formulated and produced along with the experimental diets which included 300 g/kg of each ingredient and 700 g/kg of the basal diet. Juvenile shrimp (initial mean weight: 12 g, six shrimp/tank, n = 3) were stocked in a recirculation system. Apparent dry matter, protein and energy digestibility coefficients ranged from −40.11% to 78.51%, 15.17% to 97.03% and 13.33% to 82.56% among different protein sources, respectively. In general, protein and energy digestibilities in soy sources (77.6% to 97.03% and 62.77% to 82.56%, respectively) are higher than the tested animal protein (51.39% to 71.41% and 45.29% to 69.77%, respectively) and single‐cell protein sources (15.17% to 53.47% and 13.33% to 40.39%, respectively). Among the three soybean sources, TSBM showed highest protein and energy digestibility. Apparent individual amino acid digestibility coefficients were also variable among different types of ingredients, and there was a reasonable correspondence to protein digestibility. The most digestible feed ingredients for Pacific white shrimp in this study were conventional soybean meal (SBM) and NutriVance soybean meal (NSBM), which indicated that these ingredients are good protein and amino acid sources for Pacific white shrimp. Resultant digestibility data may provide useful information to commercial shrimp feed industry.